Parameter study for WinDAM using DAKOTA - Bhat, Ashwin Ramachandra (Kansas State University, 2014)
Windows[superscript TM] Dam Analysis Modules (WinDAM) is a set of modular software components that can be used to analyze overtopped earthen embankments and internal erosion of embankment dams. Sandia National Laboratories’ DAKOTA (Design Analysis Kit for Optimization and Terascale Applications) toolkit provides algorithms to perform iterative analysis with the help of built-in algorithms for uncertainty quantiﬁcation with sampling and parameter study methods. This software integrates Sandia National Laboratories’ DAKOTA software suite with WinDAM. It provides a user-interface for input and manipulation of parameters and performs various (centered and multi-dimensional) parameter studies on a wide range of parameters. This software takes advantage of the various algorithms present in DAKOTA to perform parameter studies on the various properties of WinDAM and provides users with detailed output on the changes caused by these variations.
Keywords: WinDAM; DAKOTA; Parameter Study; Computer Science (0984)